Left coronary sinus of valsalva aneurysm dissecting into interventricular septum: a case report - Zhang, Lei; Ji, Dong-hui; Li, Xiao-yun; Liang, Kuo-peng (Journal of cardiothoracic surgery, 2024)
Background Sinus of Valsalva aneurysm (SVA) is an extremely rare condition, and its rupture causes acute symptoms such as chest pain and dyspnea. Ruptured SVA is frequently associated with other congenital defects. Case presentation A 37-year-old male presented with SVA originating from the left coronary sinus that ruptured into the interventricular septum. SVA was diagnosed by echocardiography, cardiac computed tomography and magnetic resonance imaging, and confirmed during the operation. Conclusions SVA is a rare cardiac abnormality which can lead to severe clinical symptoms upon rupture. Immediate surgery is necessary to repair the ruptured SVA.